Widespread synchrony in phosphorus concentrations in northern lakes linked to winter temperature and summer precipitation - Isles, Peter D. F.; Creed, Irena F.; Hessen, Dag Olav; Kortelainen, Pirkko; Paterson, Michael; Pomati, Francesco; Rusak, James A.; Vuorenmaa, Jussi; Bergström, Ann-Kristin (Limnology and Oceanography Letters, 2023)
Abstract In recent years, unexplained declines in lake total phosphorus (TP) concentrations have been observed at northern latitudes (> 42°N latitude) where most of the world's lakes are found. We compiled data from 389 lakes in Fennoscandia and eastern North America to investigate the effects of climate on lake TP concentrations. Synchrony in year‐to‐year variability is an indicator of climatic influences on lake TP, because other major influences on nutrients (e.g., land use change) are not likely to affect all lakes in the same year. We identified significant synchrony in lake TP both within and among different geographic regions. Using a bootstrapped random forest analysis, we identified winter temperature as the most important factor controlling annual TP, followed by summer precipitation. In Fennoscandia, TP was negatively correlated with the winter East Atlantic Pattern, which is associated with regionally warmer winters. Our results suggest that, in the absence of other overriding factors, lake TP and productivity may decline with continued winter warming in northern lakes.